Character and Property Evaluation of Sacred Fig Tree (Ficus religiosa L.: Moraceae) Wood - Thanomchat, Piyanan (Microscopy and Microanalysis Research – The Journal of The Microscopy Society of Thailand, 2019)
Wood of Ficus religiosa L. was collected from the old trunk. The anatomical character of wood was analysed to evaluate its properties. The permanent slides of wood samples were made using a sliding microtome and tissue maceration methods. The specimens were observed under light microscope and scanning electron microscope. It was found that the wood is diffuse porous with solitary and multiple pores. Tyloses are present in vessels. Rays are uniseriate heterocellular and multiseriate heterocellular (Krib’s Type II). Axial parenchyma are banded paratracheal. Starch grains are observed in axial parenchyma. Fibers are septate libriform. In term of property, wood is light when dry and has a low hardness. From the results, it can be concluded that Ficus religiosa L. wood has a potential for mushroom cultivation and furniture making but not suitable for heavy construction.